Development of Islamic Religious Education Learning in Forming Moderate Muslims - Yasin, A. Fatah; Chakim, Abdulloh; Susilawati, Samsul; Muhammad, Suaib H. (Pascasarjana Universitas KH. Abdul Chalim, 2023)
This study aims to examine the implementation of moderate Islamic values ​​in PAI learning amidst the COVID-19 pandemic at Islamic universities. The implementation of moderate Islamic values ​​in PAI learning during the covid-19 pandemic was carried out online using WhatsApp group media, YouTube. Online media is one of the forums used by lecturers and students to implement moderate Islamic values ​​in PAI learning. The method used in this research is qualitative method. Data was collected through observation, interviews, and documentation with descriptive-analytic analysis techniques. Research informants are PAI Lecturers, Students. The study was conducted in the even semester of 2020/2021 in January-June 2021 during the COVID-19 pandemic. The results of the study are that: (1) during the covid-19 pandemic the process of implementing moderate Islamic values ​​(wasathiyah) about al-adl (justice), al-tawazun (balance), and al-tasamuh (tolerance) has been good and stable. takes place in PAI learning by using online, 2) Implementation of PAI learning by using online learning media WhatsApp, youtube increases the cognitive, affective aspects of students about Islamic moderation values. (3) the success of inculcating moderate Islamic values ​​is reflected in the results of the evaluation of student learning and behavior in the good category in the Department of Islamic Education, Faculty of Tarbiyah Sciences (FITK) State Islamic University of Malang.